Rezkova věcnost a její techniky - Kolman, Vojtěch (Filosoﬁcký časopis)
The essay reconstructs the notion of “matter-of-factness” (Sachlichkeit, věcnost) in Petr Rezek’s philosophy and its roots in the immanence of our experience – or more precisely, in the tension generated by two requirements that are bound to it: (1) the thing’s (or fact’s) dependence on its appearance and (2) its difference from the appearance. These requirements create the need for immanent techniques for approaching the thing, should we wish to understand it without either overlooking or outright destroying. The notion of kitsch, in contrast to the notion of art on the one hand and matter-of-factness on the other, proves crucial for identifying these techniques. By elaborating on this contrast, we finally arrive at a direct identification of matter-of-factness with the notion of tension, as Rezek does in his late philosophy in the context of Hermann Schmitz’s “new phenomenology.”